End-of-life care: A qualitative study comparing the views of people with dementia and family carers. (March 2018) - Poole, Marie; Bamford, Claire; McLellan, Emma; Lee, Richard P; Exley, Catherine; Hughes, Julian C; Harrison-Dening, Karen; Robinson, Louise
Background: In recent years, UK policy has increasingly recognised the importance of end-of-life care in dementia. While professional consensus on optimal palliative care in dementia has been reported, little is known about the perspectives of people with dementia and family carers. Aim: To compare the views of people with dementia and family carers of people with dementia (current and recently bereaved) on optimal end-of-life care. Design: Qualitative interviews (32) and a focus group were conducted. Data were thematically analysed. Setting/participants: Participants comprised people with early stage dementia, living at home in the north-east of England ( n = 11); and current and bereaved carers ( n = 25) from six services providing end-of-life care in England. Findings: Seven areas were identified as important to end-of-life care for people with dementia and/or family carers. People with dementia and carers expressed the need for receiving care in place, ensuring comfort and a skilled care team. However, they disagreed about the importance of planning for the future and the role of families in organising care and future decision-making. Conclusion: Further comparison of our findings with expert consensus views highlighted key areas of divergence and agreement. Discordant views concerning perceptions of dementia as a palliative condition, responsibility for future decision-making and the practical co-ordination of end-of-life care may undermine the provision of optimal palliative care. Professionals must explore and recognise the individual perspectives of people with dementia and family carers.